an introduction to Medicinal Chemistry. - Patrick, Graham L. (Oxford University Press, 2023)
The author's renowned clarity of writing and the book's logical structure help to address the challenges of teaching and studying Medicinal Chemistry New chapters on Protein Kinase and Antibodies provide insightful, up-to-date coverage of some of the most significant topics in the subject today The pedagogical features enhance student engagement, which supports better knowledge retention and a more confident application of concepts and ideas to unfamiliar problems Boxes and case studies support a real-life applied approach that helps lecturers to show how theoretical content relates to the practical reality of medicinal chemistry Full-color images throughout the new edition enhance the student experience by helping them to better visualize the concepts presented New and updated exercises, questions, and activities throughout the book and online help students to hone their problem-solving skills Also available as an e-Book with functionality, navigation features, and links that offer extra learning support New to this Edition: